2021
DOI: 10.3390/foods10102295
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Phenolic Characterization and Antioxidant Bioactivity of Extracts from Edible Acheta domesticus

Abstract: With entomophagy gaining popularity in the Western hemisphere as a solution for future food insecurity, research on alternative protein sources, such as edible insects, has become relevant. Most of the research performed on insects has been on their nutritional qualities; however, little is known regarding bioactive compounds, such as polyphenols, that, if present in the insect, could provide additional benefits when the insect is consumed. In this study, methanolic extracts of Acheta domesticus from two farms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 45 publications
4
32
2
Order By: Relevance
“…The IC 50 measured by Q-ABTS was 0.434 mg/ml and for Q-DPPH was 0.677 mg/ml, respectively. These values were higher than those reported by Nino et al (2021), who found an IC 50 of 0.06 mg/ ml and 0.346 mg/ml for ABTS and DPPH, respectively, for AD extracts. These differences could be attributed to the cricket process postharvest treatment; Nino et al (2021) evaluated the antioxidant capacity of freeze-dried crickets, a process by which the antioxidant compounds of AD can be better preserved.…”
Section: Nutritional Composition Of Ad Flourcontrasting
confidence: 76%
See 1 more Smart Citation
“…The IC 50 measured by Q-ABTS was 0.434 mg/ml and for Q-DPPH was 0.677 mg/ml, respectively. These values were higher than those reported by Nino et al (2021), who found an IC 50 of 0.06 mg/ ml and 0.346 mg/ml for ABTS and DPPH, respectively, for AD extracts. These differences could be attributed to the cricket process postharvest treatment; Nino et al (2021) evaluated the antioxidant capacity of freeze-dried crickets, a process by which the antioxidant compounds of AD can be better preserved.…”
Section: Nutritional Composition Of Ad Flourcontrasting
confidence: 76%
“…On the other hand, a recent study by Nino et al (2021) found 1.9-2.1 g/100 g of TPC. These authors analyzed the AD extracts using UPLC-MS/MS and found 17 phenolic compounds being 4-hydroxybenzoic, p-coumaric, ferulic, and syringic acids the main compounds.…”
Section: Nutritional Composition Of Ad Flourmentioning
confidence: 84%
“…In addition to fermentation, methods like enzymatic proteolysis, microwave-extraction, ultrasonication, and high-pressure processing are capable of releasing bioactive compounds such as peptides, phenolic compounds, and chitin that can have potential benefits to human health in the prevention or control of diseases such as hypertension, inflammation, and type-II diabetes ( Hall & Liceaga, 2020 ). For example, edible cricket chitosan obtained from the chitin, a by-product of the protein extraction using microwave-assisted enzymatic proteolysis, was shown to have antimicrobial and hypolipidemic activity comparable to that of commercial shellfish chitosan ( Malm & Liceaga, 2021 ); whereas some phenolic compounds with antioxidant and antimicrobial activity were successfully extracted and characterized from farmed edible crickets ( Nino, Reddivari, Ferruzzi, & Liceaga, 2021 ).…”
Section: Traditional Methods and Commercial Processing Technologies U...mentioning
confidence: 99%
“…Other safety concerns are related to the anti-nutrient content in some edible insect species. Due to insects’ herbivore feeding behavior, farmed insects are primarily fed plant-based diets rich in allelochemicals such as phenolic compounds ( Nino et al, 2021 ). These allelochemicals can be a good source of antioxidants, but some can also have anti-nutritive effects.…”
Section: Challenges and Future Prospects Of Insect Proteinmentioning
confidence: 99%
“…There are many phenolic compounds with different structures, each serving a function within the plant. They are known to be involved in structural support, protection from ultraviolet ( ) radiation, defense against herbivores, inhibition of growth to nearby plants, and many more critical functions within the plant system ( Laura et al, 2019 ; Nino et al, 2021 ). The structures of phenolic compounds lead to their function not only in plants but also within the human body, once they are consumed.…”
Section: Application Of C Elegans To Study Bioacti...mentioning
confidence: 99%